The Use of Economic Geography Theory in the Study of City History, a Methodological Thinking (History Department, Semarang State University and Historian Society of Indonesia, 2022)
The study of city history requires auxiliary science to explain socio-economic phenomena. One of the essential auxiliary sciences is Geography. This article aims to describe a theoretical analysis of economic geography concepts and theories that can be used to analyze historical phenomena that discuss space as a factor in social phenomena. The research method used is a literature study based on relevant scientific books and journals. The results show that the theory and concept of geography can clarify historical researchers in discussing urban spatial phenomena related to various aspects of social phenomena, primarily the phenomenon of economic development. The images of the geographic theory that can be used are the theory of transportation networks, linkage theory, network theory or “networks,” and agglomeration theory. Through theoretical clarity, one can understand social phenomena in historical situations at a certain period more clearly than narrative studies based solely on historical sources. Kajian sejarah kota memerlukan ilmu bantu untuk menjelaskan fenomena fenomena sosial-ekonomi. Salah satu ilmu bantu penting adalah Geografi. Artikel ini bertujuan untuk memaparkan kajian teoretik konsep dan teori Geografi ekonomi yang dapat digunakan untuk menganalisis fenomena sejarah yang membahas keruangan sebagai faktor fenomena sosial. Metode penelitian yang digunakan adalah studi pustaka dengan mendasarkan pada buku dan jurnal ilmiah yang relevan. Hasil penelitian menunjukkkan bahwa teori dan konsep Geografi dapat memperjelas peneliti sejarah dalam membahas fenomena keruangan kota yang terkait dengan berbagai aspek fenomena sosial, terutama fenomena perkembangan ekonomi. Konsep dari teori geografi yang dapat digunakan adalah teori tentang jaringan transportasi, teore linkage, teori jaringan atau “networks’, dan teori aglomerasi. Melalu kejelasan teoretik maka fenomena sosial dalam situasi sejarah pada periode tertentu dapat dipahami lebih jelas dibandingkan dengan kajian naratif semata yang mendasarkan pada sumber-sumber sejarah. Cite this article: Hartatik, E.S. (2022). The Use of Economic Geography Theory in the Study of City History, a Methodological Thinking. Paramita: Historical Studies Journal, 32(2), 191-201. http://dx.doi.org/10.15294/paramita.v32i2.35611